Insight into the phylogeny and antibiotic resistance of Pseudomonas spp. originating from soil of the Białowieża National Park in Northeastern Poland - Lewandowska, Wioleta; Mahillon, Jacques; Drewnowska, Justyna Małgorzata; Swiecicka, Izabela (Frontiers in Microbiology, 2025)
The Pseudomonas genus includes species present in various environments and known for antibiotic resistance. However, only hospital-associated Pseudomonas aeruginosa have been extensively studied regarding antibiotic resistance. Thus, to fill the gap in knowledge on antibiotic resistance among other Pseudomonas spp., we investigated 41 isolates from soil samples taken in the Białowieża National Park in Northeastern Poland. This unique forest without notable anthropogenic influence, provides excellent conditions for research of antibiotic resistance from the perspective of natural environments. The phylogeny trees obtained based on the nucleotide sequence of the 16S rRNA gene and gyrB gene grouped the isolates into clusters belonging to the Pseudomonas fluorescens, Pseudomonas koreensis, and Pseudomonas putida groups, originating from the P. fluorescens lineage. All isolates under study demonstrated resistance to at least 12 out of the 24 antibiotics tested. Resistance to colistin, cefotaxime, and imipenem was detected in 73, 73, and 17% of the isolates, respectively. Most isolates showing resistance to imipenem and colistin clustered within the P. fluorescens group. Seven isolates were highly multi-resistant, to up to 18 of the 24 antibiotics tested. The presence of resistance genes related to intrinsic resistance of P. aeruginosa has been confirmed in environmental isolates.